PENGALAMAN TRAUMATIS PADA WANITA YANG MENGALAMI KEGUGURAN BERULANG - Genesis Philia Wijaya; Erlyn Erawan (Universitas Katolik Widya Mandala Surabaya, 2018)
Miscarriage is an event of fetal death without any element of intention before the time of birth. Within time, miscarriages can happen recurrently in some women. When experiencing recurrent miscarriage, individuals generally feel sad and disappointed because their hope to have a child has been lost. Recurrent miscarriages experienced by women can lead to trauma, which is the fear and insecurity that the individual feels from traumatic events. The purpose of this study is to describe the traumatic experience of a woman who has experienced recurrent miscarriage. This study used the qualitative research method and phenomenological approach. Data collection was done by interviewing three informants who suffered recurrent miscarriages of at least 3 times. The feelings seen in this study are generally sad, dissappointed and guilty from the miscarriage. The traumatic experiences that came up in the three informants were different. During handling trauma, the informants continue to believe in God for their recurring miscarriages. The informants received social support from family and spouse. During facing their trauma, the informants need social support that became useful to minimize fear and insecurity that exist in them. Social support makes informants able to accept the condition of recurrent miscarriage and reduce the trauma. Two of the three informants got pregnant again and were able to make their fetus survive after receiving social support, especially the support of their husband. Keywords: Traumatic event, women, recurrent miscarriage